2016
DOI: 10.18632/oncotarget.13175
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 13 expression reprograms bone and brain metastases of human prostate cancer cells

Abstract: Lethal progression of prostate cancer metastasis can be improved by developing animal models that recapitulate the clinical conditions. We report here that cytokeratin 13 (KRT13), an intermediate filament protein, plays a directive role in prostate cancer bone, brain, and soft tissue metastases. KRT13 expression was elevated in bone, brain, and soft tissue metastatic prostate cancer cell lines and in primary and metastatic clinical prostate, lung, and breast cancer specimens. When KRT13 expression was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 47 publications
2
32
1
Order By: Relevance
“…22 ). KRT13 was upregulated in one of the factors and has recently been associated with poor prognosis in metastatic patients 51 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…22 ). KRT13 was upregulated in one of the factors and has recently been associated with poor prognosis in metastatic patients 51 .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…A recent study similarly identified KRT13 as enriched in human fetal prostate epithelial cells and confirmed it as a marker for the stem/progenitor population in adult prostate tissue (Liu et al, 2016). Of note, KRT13 plays a directive role in prostate cancer metastasis and its expression in primary prostate tumors is predictive of metastasis and lower survival (Li et al, 2016). Little is known about PRAC1 , which encodes a small nuclear protein in human prostate and bladder cancer with prognostic capability (Kim et al, 2015; Lenka et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, FK866, a non-competitive highly specific inhibitor of NAMPT, shows potent anti-tumor activity both in vitro and in vivo [ 61 ] on pancreatic cancer samples overexpressing NAMPT mRNA. Among the other genes of our signature upregulated in STS samples are C16orf74 and KRT13 , which are associated with poor OS in pancreatic [ 62 ] and prostate [ 63 ] cancers.…”
Section: Discussionmentioning
confidence: 99%